Assessment of Selected Heavy Metals Content in Soil of Agricultural Activity - Świdwa-Urbańska, Joanna; Zalewski, Marcin (Geomatics and Environmental Engineering, 2019)
A representative sample of agricultural soil was studied for assessing the level of toxic heavy metals that could be passed on to crops; this can be the first step towards determining the possibility of its further use, especially in areas where strong industrialization progress is visible. The soil texture, pH, and bulk density along with the total amount of lead (Pb), cadmium (Cd), and nickel (Ni) were analyzed for characterizing the status of the soil at two depths: TOP (a composite sample from 0‑30 cm deep) and BOTTOM (a composite sample from 30‑60 cm deep). The sampling scheme was a square grid with 16 regularly spaced points. The heavy metals concentration values were below legal limits but higher than the regional geochemical background level, suggesting an anthropogenic origin. The pollution load index (PLI) was implemented as a tool for computing the generalized heavy metal pollution status. A geostatistical analysis of the data shows a spatial variation on a detailed scale, both in the horizontal and vertical dimensions, with the TOP soil showing higher average Pb and Cd concentrations.